Pengaruh Edukasi dan Program Diet Terhadap Perubahan Indeks Massa Tubuh dan Lingkar Perut Pada Obesitas Dewasa - Rahayu, Leni Sri; Linda, Ony (UHAMKA PRESS, 2024)
Obesity is a major risk factor for the emergence of degenerative diseases. Screening results for UHAMKA lecturers and education staff in 2021 showed that 31.1% and 57.2% were obese based on Body Mass Index (BMI) and waist circumference (WC). This study aims to analyze the effect of nutritional education and diet programs on weight loss, BMI, and WC. This is experimental research One Group Pretest Posttest Design. The intervention provided was nutritional education and a diet program in the form of reducing energy by 500 kcal/day and providing lunch for 6 consecutive days. The variables measured were body weight, BMI, WC, knowledge, attitudes, and behavior of balanced nutrition. Attitude and behavior variables on balanced nutrition were assessed using a questionnaire. A 24-hour recall was carried out to see the subjects' eating patterns before and after the intervention. The statistical tests used were the Wilxocon test and Paired t test to see differences in BMI, WC, attitudes, and behavior on balanced nutrition before and after the intervention. The research results showed that there was an average reduction in body weight, BMI, and WC. The results of statistical tests using the paired t test showed that there was a significant difference in WC before and after the intervention (p=0.000). Female subjects showed significant differences in body weight, BMI, and WC. It was found that there was an increase in knowledge scores, attitudes, and behavior of balanced nutrition. Education and diet programs influenced changes in the nutritional status of subjects.